2018
DOI: 10.1136/bjsports-2017-097839
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb biomechanics in femoroacetabular impingement syndrome: a systematic review and meta-analysis

Abstract: CRD42016038677.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 47 publications
(70 reference statements)
4
81
0
Order By: Relevance
“…Changes in movement patterns and biomechanics have been reported in people with FAIS [5,6]. Diamond [5] found that individuals with FAIS demonstrated greater hip and lumbo-pelvic asymmetries, including lateral trunk lean, pelvic rise and hip abduction, in a step-up task compared to unaffected individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in movement patterns and biomechanics have been reported in people with FAIS [5,6]. Diamond [5] found that individuals with FAIS demonstrated greater hip and lumbo-pelvic asymmetries, including lateral trunk lean, pelvic rise and hip abduction, in a step-up task compared to unaffected individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Diamond [5] found that individuals with FAIS demonstrated greater hip and lumbo-pelvic asymmetries, including lateral trunk lean, pelvic rise and hip abduction, in a step-up task compared to unaffected individuals. King's [6] systematic review on lower limb biomechanics in FAIS highlighted individuals with FAIS had less hip extension, total hip range in the sagittal plane and peak hip internal rotation during walking and did not squat as deeply, although hip flexion range in the squat was same as controls. These findings illustrate hip biomechanical impairments in FAIS and the need for individualized assessment to gain an understanding of a person's movement patterns and pain presentation Pain in FAIS is typically motion-related or position-related [1].…”
Section: Introductionmentioning
confidence: 99%
“…Peak muscle activity in this study occurred at the lowest point during the squatting task (50% of the movement cycle). Anterior pericapsular muscles were not expected to play a role in torque production during squatting, 251 due to their location anterior to the axis or rotation. Therefore, this pattern of activity has the potential to correspond with active tensioning of the capsule approaching positions of impingement or in co-contraction of pericapsular muscles to assist in joint control.…”
Section: Discussionmentioning
confidence: 99%
“…Longer stride lengths without any alteration in muscle activity could identify a potential driver of symptoms and pathology, early in the spectrum of non-arthritic hip-related pain, with shortened strides being the preferred strategy to limit translation in later stages of pathology. 251 There are several factors that could also contribute to the findings of no difference in activity of iliocapsularis, iliacus, gluteus minimus and rectus femoris, during walking between FAI syndrome and asymptomatic controls (study 4). People with FAI syndrome, although hypothesised to have subtle instability, may not be sufficiently compromised to require additional active control.…”
Section: Dynamic Hip Stabilitymentioning
confidence: 97%
“…Hip ROM deficits are also reported in individuals with hip pain when compared to asymptomatic controls [64,67,81,119]. Functionally, the presence of hip pain affects lower limb reaching, forward stepping and squatting, and there is evidence that dynamic single leg balance is affected within individuals who have undergone arthroscopy to address hip chondropathy [84,129].…”
Section: Impairments Associated With Hip Pathologymentioning
confidence: 99%